What are the benefits of antenatal education as a maternal health promotion tool? A systematic review with meta-analysis - Zanetti, Miriam Raquel Diniz; Sosa, Claudio; Foster, Thais; Rossello, Jose Luis; Serruya, Suzanne; Múcio, Bremen de (ABCS Health Sciences, 2024)
Introduction: Antenatal education is a low-cost intervention designed to increase the knowledge of pregnant women on pregnancy and childbirth and reduce fear related to labor pain. However, the impact of antenatal education programs on maternal outcomes is unclear. Objective: To investigate whether structured antenatal education programs affect maternal health outcomes. Methods: Electronic databases were searched from inception to November 2019, and randomized controlled trials investigating antenatal educational programs for low-risk pregnant women were included. Results: A total of 348 studies were identified; nine were included in this review. One study assessed the number of antenatal visits, while three showed that antenatal education programs significantly improved childbirth self-efficacy (outcome expectancy16.00 [95% CI 9.86-22.15] and efficacy expectancy 20.44 [95% CI=13.62-27.25]). Self-diagnosis on labor was investigated in two studies, and five demonstrated that antenatal education increased the frequency of vaginal delivery (odds ratio 1.28 [95% CI 1.01-1.63]) but not episiotomy (as observed in three studies). Conclusion: Structured antenatal education programs may increase childbirth self-efficacy and the frequency of vaginal delivery.